Association between patient's expectations and real outcomes for degenerative spine surgery. - Joana Araújo de Azevedo (2020)
Purpose: The aim of this study is to compare patient's expectations before surgery for degenerative spine disease to postoperative perceived outcomes and identify main factors that correlate with higher expectations and their fulfillment. The study question is whether patient's pre-surgical expectations can predict actual outcomes. Methods: Consecutive patients submitted to degenerative spine surgery between August 2018 and May 2019 in our spine center were enrolled. Patient's expressed expectations were recorded using the Lumbar/Cervical Spine Surgery Expectations Survey and compared to the same instrument, three months after surgery. Patient reported outcomes were evaluated using the COMI questionnaire before and after surgery. Results: A total of 120 patients were analyzed. The mean score of expectations reported by patients was 82.87%±14.57% and post-surgical score was significantly lower, 60.5±20.6% (p<0.001). In a multivariate analysis, only a history of spine surgery and a longer duration of symptoms were associated with low pre-surgical expectations. Lumbar surgery was associated to a lower ratio between postoperative and preoperative Expectations Survey scores. An improvement on the COMI score after surgery was achieved in 85% of the patients, but only 14% reported that their expectations were matched or exceeded. Conclusion: The pre-surgical expectations were significatively high, but the post-surgical results were less optimistic. Lower expectations and lower perceived success after surgery can be anticipated on some patients based on preoperative features. Although 85% of patients improved after surgery, their expectations weren't met in most cases.